2018
DOI: 10.2217/imt-2017-0177
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Mesothelioma Clinical Trial Combines Immunotherapy Drugs

Abstract: " while the full published results from MAPS2 and NIBIT-Meso1 studies are still pending, the use of combined checkpoint inhibitors appears promising for mesothelioma. The approach opens many potential therapeutic avenues for advanced mesothelioma. "Immunotherapy by checkpoint inhibitor is effective for a number of solid tumors including malignant mesothelioma. Studies utilizing single-agent PD-1 or PD-L1 inhibitor for mesothelioma have reported tumor response rates in approximately 10-20% of patients treated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Immune checkpoint inhibitors targeting the PD-L1/PD-1 pathway have recently been used to treat advanced MPM, and the efficacy is being investigated in several clinical trials. Some patients with advanced MPM benefited from immunotherapy with anti-PD-L1/PD-1 inhibitors [14,15,16,17,30,31,32,33]. A phase II clinical trial (NCT02628067; KEYNOTE-158) to investigate the efficacy of pembrolizumab (anti-PD-1) in advanced solid tumors, including MPM, is ongoing; patients are encouraged to participate in this trial to facilitate advancement in the treatment of MPM.…”
Section: Programmed Death-ligand 1 In Non-small Cell Lung Cancer Amentioning
confidence: 99%
“…Immune checkpoint inhibitors targeting the PD-L1/PD-1 pathway have recently been used to treat advanced MPM, and the efficacy is being investigated in several clinical trials. Some patients with advanced MPM benefited from immunotherapy with anti-PD-L1/PD-1 inhibitors [14,15,16,17,30,31,32,33]. A phase II clinical trial (NCT02628067; KEYNOTE-158) to investigate the efficacy of pembrolizumab (anti-PD-1) in advanced solid tumors, including MPM, is ongoing; patients are encouraged to participate in this trial to facilitate advancement in the treatment of MPM.…”
Section: Programmed Death-ligand 1 In Non-small Cell Lung Cancer Amentioning
confidence: 99%
“…Anti-PD-1 and anti-PD-L1 immunotherapy protocols (such as nivolumab or pembrolizumad) have been developed and used to restore immune edition in cancers [ Figure 2]. This process is called immune checkpoint blockade (ICB) and, in the last few years, this new treatment has been tested and shown promising results in many different types of cancers such as: non-small cell lung carcinoma (NSCLC), melanoma, mesothelioma, renal cell carcinoma (RCC), bladder cancer, head and neck squamous cell carcinoma (HNSCC) [14][15][16][17][18][19] . Unfortunately, although some very interesting results were obtained in some patients, resistance to ICB are observed in a large percentage of cases.…”
Section: Resistance To Immunotherapy In Cancersmentioning
confidence: 99%
“…Our second-most-read article was an editorial that evaluated the effect that combining immunotherapy checkpoint inhibitors PD1, PD-L1 and CTLA-4 have on mesothelioma [2]. Written by Monica Chatwal et al, this article concluded that this method of treatment is showing promise but further study is needed.…”
Section: Content Highlightsmentioning
confidence: 99%